GENERATOR POLYNOMIAL OF IDEAL IN POLYNOMIAL RING AND ITS RELEVANCE TO CYCLIC CODE - Tuhfatul Janan; Syifaul Janan; Sri Wigantono (PT Innovative Academic Journals, 2025)
Cyclic codes were discovered by Prange in 1957. They have served as the foundation for the development of modern coding theory, such as Hamming codes, Golay codes, Reed-Solomon codes, and others. Cyclic codes are closely related to generator polynomials of a polynomial ring. This research uses a literature review method using relevant international articles and books. The research will revisit several aspects of Ling and Xing's work on generator polynomial of ideal in polynomial ring and its relevance to cyclic code. Furthermore, detailed explanations will be provided along with several examples.